Business Plan on Al-Qudsi Day Care - Qudsi, Diana Kholifatul; Herliana, Sri (Journal of Business and Management, 2015)
Abstract - Daycare is a child social service that provides services to children aged 6 months to 5 years old before the form, treatment, care, nutrition, social guidance, counseling mental, spiritual, educational stimulation, and games. Currently Daycare is one alternative to parents who have busy outside the home in actualizing science and its role in the community. Therefore the aim of this paper the author makes is what potential and challenges in doing business Daycare.The method used by the authors in this study is the use literature and case study of Al-Qudsi Daycare is located at Jl. Saturnus Utara No. 55, Bandung, 40295. Al-Qudsi Daycare is a start-up business that is made by the author as student of entrepreneur tracks program at School of Business and Management ITB.From the results of this paper the authors find that the potential of Al-Qudsi Daycare is about effort of marketing with big respond and financial condition that prospective. The challenges of Al-Qudsi Daycare are so many competitors and claim of desire from consumers increase. Recommendation from author is Al-Qudsi Daycare must develop of strategy marketing and financial marketing and provide the technology for facilities so that secure and pleasant.Keywords: Daycare, net present value, rate of return, payback period, plans and marketing strategies, opportunities, and challenges.